Depression Status, Lifestyle, and Metabolic Factors With Subsequent Risk for Major Cardiovascular Events: The China Cardiometabolic Disease and Cancer Cohort (4C) Study - Chen, Xi; Liu, Zhelong; Yang, Yan; Chen, Gang; Wan, Qin; Qin, Guijun; Yan, Li; Wang, Guixia; Qin, Yingfen; Luo, Zuojie; Tang, Xulei; Huo, Yanan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: We aimed to evaluate the association between depression and major cardiovascular events and test whether the depression-cardiovascular relationship is influenced by lifestyle or metabolic risk factors. Methods: The China Cardiometabolic Disease and Cancer Cohort (4C) Study was a nationwide, multicenter, prospective cohort study. 92,869 participants without cardiovascular disease or cancer at baseline were included. Depression status was evaluated by the Patient Health Questionnaire-9. Lifestyle information was collected by questionnaire, and metabolic risk factors including waist circumference, blood pressures, lipid profiles, and plasma glucose were measured. Major cardiovascular events including cardiovascular death, myocardial infarction, stroke, and hospitalized or treated heart failure were validated based on medical records. Results: During an average of 3.8 years follow-up, we detected 2,076 cardiovascular events and showed that participants with depression symptom had an increased risk for cardiovascular events after adjustments (HR: 1.29; 95% CI: 1.08-1.52). Stratified on lifestyle risk, depression was associated significantly with the risk of cardiovascular events only in participants with medium lifestyle risk (HR: 1.39; 95% CI: 1.09-1.76). As to metabolic risk status, the depression-cardiovascular relationship tended to be stronger according to the increasing numbers of metabolic risk factors, with HR (95% CI) of 0.98 (0.71-1.34) in the category with 0-2 metabolic risk factors, 1.37 (0.998-1.87) and 1.49 (1.14-1.94) for those with 3, and 4-5 metabolic risk factors, respectively, indicating an interaction effect (P = 0.035). Conclusions: Depression was independently associated with an increased risk of major cardiovascular events. The effect was particularly prominent among population at higher metabolic risk.